Influence Evaluation of Sensor Coordinate Error on Microseismic Source Location - Li, Tao; Chen, Bing-Rui; Wang, Qing; Zhu, Xin-Hao; Wang, Xu; Xie, Ming-Xing (Frontiers in Earth Science, 2022)
In microseismic (MS) source localization, it is usually assumed that the sensor coordinates are accurate. However, there are generally measurement errors for the sensor coordinates in practical engineering, which severely affect the location accuracy of the MS sources. Therefore, based on the least square linear inversion equation, the theoretical analysis shows that the location error is proportional to the sensor coordinate error. To reduce the systematic error of the MS source location, a calculation method for the sensor coordinate error threshold is proposed. First, the theoretical arrival time of each sensor is calculated. Then, the sensor coordinate error is added and combined with the original sensor coordinate for location. Finally, the sensor coordinate error threshold that makes the location results reach the source location accuracy is obtained. Furthermore, based on this method and assuming that the sensor coordinate error is in a normal distribution, a comprehensive evaluation index of the sensor coordinates is proposed to evaluate the influence of the sensor coordinates on the MS source location. The application results of the Beiminghe Iron Mine in Hebei Province show that the farther the source is from the sensor array, the smaller the sensor coordinate error threshold is. The sensor coordinate error threshold in the sensor array is larger than that outside the sensor array. The sensor coordinate error threshold decreases rapidly in the sensor array and slowly outside the sensor array. After removing sensor No. 201, which has the greatest influence on MS source location and has a large measurement error, the average location accuracy of blasting test events is improved by 25.74%. The research results have a certain guiding significance for the sensor coordinate measurement.